The detection and localization of monocyte chemoattractant protein-1 (MCP-1) in human ovarian cancer. - Negus, R P (1995)
Chemokines may control the macrophage infiltrate found in many solid tumors. In human ovarian cancer, in situ hybridization detected mRNA for the macrophage chemokine monocyte chemoattractant protein-1 (MCP-1) in 16/17 serous carcinomas, 4/4 mucinous carcinomas, 2/2 endometrioid carcinomas, and 1/3 borderline tumors. In serous tumors, mRNA expression mainly localized to the epithelial areas, as did immunoreactive MCP-1 protein. In the other tumors, both stromal and epithelial expression were seen. All tumors contained variable numbers of cells positive for the macrophage marker CD68. MCP-1 mRNA was also detected in the stroma of 5/5 normal ovaries. RT-PCR demonstrated mRNA for MCP-1 in 7/7 serous carcinomas and 6/6 ovarian cancer cell lines. MCP-1 protein was detected by ELISA in ascites from patients with ovarian cancer (mean 4.28 ng/ml) and was produced primarily by the cancer cells. Human MCP-1 protein was also detected in culture supernatants from cell lines and in ascites from human ovarian tumor xenografts which induce a peritoneal monocytosis in nude mice. We conclude that the macrophage chemoattractant MCP-1 is produced by epithelial ovarian cancer and that the tumor cells themselves are probably a major source. MCP-1 may contribute to the accumulation of tumor-associated macrophages, which may subsequently influence tumor behavior.